Surviving the black swan, strategies for process safety specialists, and companies to survive unpredicted catastrophic events. Issue 1 (March 2016) - Murphy, John F.
Abstract : This article is a continuation of three articles that I have authored or coauthored on the "black swan, " the rare and unpredictable catastrophic event. The first two papers discussed the concept of the black swan as applied to the chemical and petroleum processing industries and the difficulty in predicting such events. The third paper discussed the fact that we have difficulty maintaining the lesson's learned from black swan events that have occurred. I have survived and witnessed several black swans. Each has affected me personally and professionally. Black swan events are rare but inevitable. Some individuals and companies survive black swan events and continue on while others do not. I have learned that many black swan events, although initially viewed as catastrophes, can result in opportunities from a process safety improvement, career, and personal perspective. This article presents examples of black swan events that have impacted my career in process safety, often in a positive way, and strategies for surviving these "black swan" events from a personal, professional, and a company point of view. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 13–17, 2016